DETERMINATION OF REPURCHASE INTENTION FOR MSMES IN BANDAR LAMPUNG - Endang Sulastri; Ni Putu Widhia Rahayu (ZILLZELL MEDIA PRIMA, 2024)
Due to intense competition in MSMEs, there are more and more MSME players. This research was conducted to explain how service quality, website quality, reputation, online shop trust affects purchase intent. To collect data, this study used a quantitative approach. With purposive sampling, with a population of 4,446 respondents and a Likert scale. The sample is calculated by the formula slovin 97. Data analysis was carried out with multiple linear tests using SPPS version 26, and hypothesis tests such as t tests and f tests were also carried out. The results showed that the variables of service quality had a positive and significant effect on purchase intent, website quality had a positive and significant effect on purchase intent, reputation did not have a positive and significant effect on purchase intent, online shop confidence had a positive and significant influence on purchase intent.